1996
DOI: 10.1111/j.1476-5381.1996.tb16015.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of celiprolol therapy on arterial dilatation in experimental hypertension

Abstract: 1 It has recently been suggested that therapy with ,B-adrenoceptor blockers reduces peripheral arterial resistance via enhanced vascular dilatation. Therefore, we studied the effects of celiprolol, which is a specific l,-antagonist that has a weak fl2-agonist action, on arterial tone in spontaneously hypertensive rats (SHR) and Wistar-Kyoto (WKY) rats. 2 Two doses of celiprolol (5 and 50 mg kg-' day-') were administered to the SHR, while the WKY rats received only the higher dose of the drug. During the 12-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…23 Moreover, the present study has shown that celiprolol exerts beneficial effects in rats with endothelial dysfunction in the early phase of hypertension. Consistent with our results, long-term treatment with celiprolol, even at its subdepressor dose (5 mg ⅐ kg Ϫ1 ⅐ d Ϫ1 PO), has been reported to restore endothelial dysfunction of mesenteric arteries of spontaneously hypertensive rats, 24 suggesting that the beneficial effects of celiprolol in hypertension are not only due to reduction in blood pressure. Therefore, stimulation of NO release caused by celiprolol may be a mechanism underlying its vascular action.…”
Section: Discussionsupporting
confidence: 79%
“…23 Moreover, the present study has shown that celiprolol exerts beneficial effects in rats with endothelial dysfunction in the early phase of hypertension. Consistent with our results, long-term treatment with celiprolol, even at its subdepressor dose (5 mg ⅐ kg Ϫ1 ⅐ d Ϫ1 PO), has been reported to restore endothelial dysfunction of mesenteric arteries of spontaneously hypertensive rats, 24 suggesting that the beneficial effects of celiprolol in hypertension are not only due to reduction in blood pressure. Therefore, stimulation of NO release caused by celiprolol may be a mechanism underlying its vascular action.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, some interventions have been effective in correcting ␤AR signaling in hypertension, such as dietary salt restriction 7 or pharmacological treatment. 11 Recently, a novel tool to modulate ␤AR signaling in a selective manner has been provided by adenoviral-mediated gene transfer of the human ␤ 2 AR cDNA. Indeed, in cardiac myocytes from both normal 12 and failing hearts, 13,14 adenoviral-mediated delivery and overexpression of the ␤ 2 AR enhanced signaling and physiological responses to ␤AR agonists.…”
mentioning
confidence: 99%
“…In some cases (e.g. relaxations to nitric oxide donor and contractions to NA) the magnitude of this variation exceeded the difference previously observed between corresponding sections of the superior mesenteric arteries from Wistar-Kyoto rats and spontaneously hypertensive rats (Kahonen et al 1995;Makynen et al 1995;Tolvanen et al 1996).…”
Section: Discussionmentioning
confidence: 79%